RANCANG BANGUN SISTEM E-LEARNING AKADEMIK BERBASIS ANDROID (Studi kasus Program Studi Sistem Informasi Unisbank Semarang) (Jurnal Dinamika Informatika, 2013)
Academic e-learning application based on Android are expected to help students, especially Studies Program Faculty of Information Systems Unisbank Information Technology in teaching and learning through e-Learning system based on Android. With this application students will be able to see the material that is given by the lecturer. In addition to looking at the materials the students can download the materials provided, make entry and update tasks and can see the value of the tasks assigned by the lecturer through Android Smartphone. This application uses a methodology that has the prototype stages of design, programming, evaluation and results. This application is built using Java, XML, and PHP. Smartphones are used in the final test version of the system are Smartphone with Android 2.2 (Froyo) or above. Keywords: Java, XML, PHP, eLearning, Android, Froyo, Smartphone.